In Vivo Kinematic Analysis of Mobile-Bearing Unicompartmental Knee Arthroplasty during High Flexion Activities - Kono, Kenichi; Yamazaki, Takaharu; Tamaki, Masashi; Inui, Hiroshi; Tanaka, Sakae; Tomita, Tetsuya (The Journal of Knee Surgery, 2024)
Mobile-bearing (MB) unicompartmental knee arthroplasty (UKA) has high conformity between the femoral articular surface and the meniscal bearing; therefore, the surface and subsurface contact stress is reduced. Additionally, the survival rate is high. However, the in vivo kinematics of MB UKA knees during high-flexion activities of daily living remain unknown. The aim of this study was to investigate in vivo the three-dimensional kinematics of MB UKA knees during high-flexion activities of daily living. A total of 17 knees of 17 patients who could achieve kneeling after MB UKA were examined. Under fluoroscopy, each patient performed squatting and kneeling motions. To estimate the spatial position and orientation of the knee, a two-dimensional/three-dimensional registration technique was used. We evaluated the femoral rotation and varus–valgus angle relative to the tibia and the anteroposterior translation of the medial sulcus (medial side) and lateral epicondyle (lateral side) of the femur on the plane perpendicular to the tibial mechanical axis in each flexion angle. From 130° to 140° of flexion, the femoral external rotation during squatting was significantly smaller than that during kneeling. Additionally, the medial side of the femur during squatting was significantly more posteriorly located compared with that during kneeling. There was no significant difference between squatting and kneeling in terms of the lateral side of the femur and the varus–valgus position in each flexion angle. At high flexion angle, the kinematics of MB UKA knees may differ depending on the performance.
Keywords: unicompartmental knee arthroplasty; kinematics; high-flexion activities; mobile-bearing